2020
DOI: 10.1038/s41598-020-75749-4
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends of care practices, morbidity, and mortality of extremely preterm infants over 10-years in South Wales, UK

Abstract: Contemporary outcome data of preterm infants are essential to commission, evaluate and improve healthcare resources and outcomes while also assisting professionals and families in counselling and decision making. We analysed trends in clinical practice, morbidity, and mortality of extremely preterm infants over 10 years in South Wales, UK. This population-based study included live born infants < 28 weeks of gestation in tertiary neonatal units between 01/01/2007 and 31/12/2016. Patient characteristics, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Despite decreasing mortality, there was less improvement in BPD. Most recent studies examining secular trends in BPD have reported unchanged or increasing rates over time 4,23,24 . In a large international cohort from 11 high‐income countries, investigators found that the rate of BPD among very preterm infants increased between 2007 and 2015 in most collaborative countries, except Canada and Finland 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite decreasing mortality, there was less improvement in BPD. Most recent studies examining secular trends in BPD have reported unchanged or increasing rates over time 4,23,24 . In a large international cohort from 11 high‐income countries, investigators found that the rate of BPD among very preterm infants increased between 2007 and 2015 in most collaborative countries, except Canada and Finland 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Most recent studies examining secular trends in BPD have reported unchanged or increasing rates over time. 4,23,24 In a large international cohort from 11 high-income countries, investigators found that the rate of BPD among very preterm infants increased between 2007 and 2015 in most collaborative countries, except Canada and Finland. 5 A retrospective cohort study in Spain revealed that BPD-free survival remained constant over the last 10 years and even worsened in the group with the lowest GA (23-25 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Avoiding MV, if possible, and optimizing noninvasive respiratory support in preterm infants reduces lung injury and improves neonatal outcomes [ 16 , 17 ].…”
Section: Noninvasive Respiratory Support Of the Preterm Infants In Th...mentioning
confidence: 99%
“…(13) However, even with the increasing usage of antenatal corticosteroids and surfactant for lung maturation, (14) the reported incidence of IVH has not consistently decreased. (15)(16)(17)(18) There have been many trials and reviews investigating the effectiveness of preventative interventions. (3,8,13) Interventions can be given antenatally to the mother, or postnatally to the infant after birth.…”
Section: Introductionmentioning
confidence: 99%